EL VALLE DE AYACUCHO Y EL TAWANTINSUYO - Valdez, Lidio M. (2002)
This paper is aimed to assess the situation of the Ayacucho Valley of the Peruvian central highlands before and during the lnka occupation. Until very recently, it was argued that this valley was largely abandoned during lnka times and consequently played no role within the lnka Empire. Because of new fieldwork carried out on the northern portion of the va/ley, it is becoming evident that in the region there were severa[ importantlnka period sites. Before the lnka conquest, the inhabitants ofthe region occupied sites established in defensive positions and often at higher elevation. Following lnka conquest, most ofthese sites were relocated to lower elevations. At the same time, the Local pre-lnka pottery style survived and continued being manufactured during lnka times, as its occurrence at both defensive sites and low elevation sites indicates. lnka related artifacts, however, are present only at lower elevation sites.